PEMBELAJARAN SENI TARI DI SMPLB BINA KARYA INSANI KARANGANYAR - Sulastuti, Katarina Indah (Institut Seni Indoensia Surakarta, 2015)
This research aims to identify a model of dance learning in SMPLB Bina Karya Insani Karanganyar. Dance learning for the special need students in SMPLB is very important for the ability and the chance to express become an activity that is able to make a strong self-confidence grows. For the reason, it is urgent to provide a special learning system for the students in order to express themselves through dance activities. The research target is identification of the dance learning model for the students in SMPLB Bina Karya Insani Karanganyar. The research uses descriptive qualitative method. The ways include: library study of learning model for dance practice; observation and exploration ofdance learning model for the tunagrahita students; descriptive qualitative analysis of dance learning model for tunagrahita students; and designing dance learning model for tunagrahita students. The research result shows that the identification of dance learning method in SMPLB Bina Karya Insani become a reference for arranging the design of dance learning model with a newmethod.Keywords: identification, learning method, dance art, SMPLB.